Effects of Lipid Overload on Heart in Metabolic Diseases - Yan, An; Xie, Guinan; Ding, Xinya; Wang, Yi; Guo, Liping (Hormone and Metabolic Research, 2021)
Metabolic diseases are often associated with lipid and glucose metabolism abnormalities, which increase the risk of cardiovascular disease. Diabetic cardiomyopathy (DCM) is an important development of metabolic diseases and a major cause of death. Lipids are the main fuel for energy metabolism in the heart. The increase of circulating lipids affects the uptake and utilization of fatty acids and glucose in the heart, and also affects mitochondrial function. In this paper, the mechanism of lipid overload in metabolic diseases leading to cardiac energy metabolism disorder is discussed.
Keywords: lipid metabolism; cardiac energy metabolism; metabolic diseases; metabolic syndrome; type 2 diabetes; diabetic cardiomyopathy